Reply to "Comment on: Decrease of anticholinergic drug use in nursing home residents in the United States". Issue 7 (30th April 2021) - Mehta, Hemalkumar B.; Malagaris, Ioannis; Goodwin, James S.
Abstract : This letter comments on the letter by Ulla Aalto .